Narrative synthesis of health service accreditation literature. Issue 12 (4th October 2012) - Hinchcliff, Reece; Greenfield, David; Moldovan, Max; Westbrook, Johanna Irene; Pawsey, Marjorie; Mumford, Virginia; Braithwaite, Jeffrey
Abstract : Aims: To systematically identify and synthesise health service accreditation literature. Methods: A systematic identification and narrative synthesis of health service accreditation literature published prior to 2012 were conducted. The search identified 122 empirical studies that examined either the processes or impacts of accreditation programmes. Study components were recorded, including: dates of publication; research settings; levels of study evidence and quality using established rating frameworks; and key results. A content analysis was conducted to determine the frequency of key themes and subthemes examined in the literature and identify knowledge-gaps requiring research attention. Results: The majority of studies (n=67) were published since 2006, occurred in the USA (n=60) and focused on acute care (n=79). Two thematic categories, that is, 'organisational impacts' and 'relationship to quality measures', were addressed 60 or more times in the literature. 'Financial impacts', 'consumer or patient satisfaction' and 'survey and surveyor issues' were each examined fewer than 15 times. The literature is limited in terms of the level of evidence and quality of studies, but highlights potential relationships among accreditation programmes, high quality organisational processes and safe clinical care. Conclusions: Due to the limitations of the literature, it is not prudent to make strong claims about the effectiveness of health service accreditation. Nonetheless, several critical issues and knowledge-gaps were identified that may help stimulate and inform discussion among healthcare stakeholders. Ongoing effort is required to build upon the accreditation evidence-base by using high quality experimental study designs to examine the processes, effectiveness and financial value of accreditation programmes and their critical components in different healthcare domains.